STUDIES ON THE GROWTH OF THE WEDGE CLAM, DONAX (LATONA) CUNEATUS LINNAEUS - Nayar, K Nagappan (Indian Journal of Fisheries, 2016)
OF the several species of wedge clams of the family Donacidce that occur on the east and west coasts of India in the surf-beaten sands, Donax scortum to some and Donax cuneatus to a very large extent are valued as food by many people. In the Palk Bay, ail along the beach from Pillaimadam shore <Long. 79Â° 5’ and Lat. 9Â° 17’) to Attankarai (Long. 79Â° 0’ and Lat. 9Â° 21’), a distance of about seven miles, the receding tides reveal Donax cuneatus in abundance.